Melanoma tipo animal: Relato de dois casos - Marques, Mariângela Esther Alencar [UNESP]; Yamashita, Thamy [UNESP]; Marques, Silvio Alencar [UNESP]; Nai, Gisele Alborghetti (My University, 2010)
A potential diagnostic pitfall in the histological assessment of melanomas is the difficulty in recognizing unusual melanoma variants. Among them, the most challenging examples comprise desmoplastic melanomas, nevoid melanomas, the so-called minimal-deviation melanoma, melanomas with prominent pigment synthesis or animal-type melanoma, and the malignant blue nevus. Two cases of animal type melanoma are reported and the importance of clinical-histopathological differential diagnosis is discussed.
Animal type melanoma: A report of two cases
Keywords: Hiperpigmentation; Melanocytoma; Melanoma; Variants